Bank managers' perceived importance of corporate environmental management in lending decisions: investigating institutional motivational factors. Issue 8 (3rd July 2022) - Qi, Junmei; Eberhardt-Toth, Edina; Paulet, Elisabeth
Abstract : This study sheds light on the perception of corporate environmental management (CEM) in the lending business from the lenders' perspective. The importance of the implementation of the CEM practices of borrowing companies indicated by bank managers is used to measure the bank managers' perceptions of CEM in lending decisions. In addition, this paper examines the influence of institutional motivations – coercive, mimetic and normative – on the perception of CEM. A survey was conducted among 110 bank managers in France and Luxembourg in 2019. Through factor analysis and regression modeling, we found that banks' CEM requirements for borrowing firms are mainly determined by pressure-type motivations, such as coercive and mimetic, rather than benefit-type motivations, such as financial and reputational. Our results offer new insights into how bank managers perceive the importance of CEM in lending decision-making and explain the perceptions that have been less studied in the existing literature.